Medical interview in the system of dental care providing to patients with special needs - Lytovchenko , V.P. (Medicni perspektivi, 2022)
Among the leading trends in the field of medicine – improving the quality of various services; focus on individually targeted care, experience and needs of patients; creating equal opportunities and favorable treatment conditions. Relevant in this context is the “Cambridge guide to the medical interview” designed to identify effective communication skills between physician and patient and to provide a sound framework for their analysis. To solve the two leading tasks, an adapted interview model for dentists was developed and tested, taking into account the communicative needs of patients with severe hearing impairment (to the general tasks of “providing structure”, “building the relationship”), which are cross-cutting for each stage of medical interview, “ensuring a universal design of the environment” included, before the stage of “initiating the session” an additional “selection of priority means of communication/necessary adaptations”, etc.) was proposed. Based on the described modern approaches to building trusting relationships in medical practice, taking into account the adapted version of the interview, the key components of working with patients with special needs (hearing impairment) in dentistry are identified.